2009
DOI: 10.1186/1757-7241-17-43
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of the systemic inflammatory response after major accidental trauma

Abstract: BackgroundThe purpose of the present study was to describe the pathophysiology of the systemic inflammatory response after major trauma and the timing of final reconstructive surgery.MethodsAn unsystematic review of the medical literature was performed and articles pertaining to the inflammatory response to trauma were obtained. The literature selected was based on the preference and clinical expertise of authors.DiscussionThe inflammatory response consists of hormonal metabolic and immunological components an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 60 publications
3
91
1
6
Order By: Relevance
“…3,5,18 We report that a single transverse laparotomy and closure with no further manipulation was associated with the following:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,18 We report that a single transverse laparotomy and closure with no further manipulation was associated with the following:…”
Section: Discussionmentioning
confidence: 99%
“…However, whether local activation develops into a systemic response depends upon the severity and duration of traumatic tissue injury. 18,27,28 The early rise of pro-inflammatory cytokine IL-6 in plasma from activated immune cells is believed to be a measure of stress severity. 29 In 2006, Ishibashi et al showed that IL-6 levels correlated with the length of surgical incision (1.0 cm vs. 3.0 cm) with the larger incision leading to doubling of plasma IL-6 values at 3 and 6 h. 30 Our study showed that plasma IL-6 increased to similar extents after 1 h in saline and ALM groups (145 AE 76 and 128 AE 66 pg/ml) (Figure 4).…”
Section: Alm Appeared To Reduce Reactive Thrombocytosis After 1 Hmentioning
confidence: 99%
“…Падение активности нейтрофилов ведет к септическим осложнениям, а гиперактивация -к развитию органной недостаточности [9]. В процессе активации нейтрофилов происходит сборка мембранной NADPH-оксидазы и запуск реакций с участием фермента МПО, содержащегося в азурофильных гранулах, результатом чего является продукция нейтрофилами активных форм кислорода ( · О 2 -, Н 2 О 2 , · ОН-радикала и др.)…”
Section: результаты и обсуждениеunclassified
“…41 A intervenção ativa neste processo de resposta do indivíduo politraumatizado é tentadora, medidas imunomoduladoras como bloqueio de receptores androgênicos, modulação de receptores "Toll Like", inibidores de dihidrotestosterona (DHT) 42 e hipotermia 43 são algumas destas propostas.…”
Section: Nefropatia Por Contraste Iodadounclassified